Achieving Ultralong‐Cycle Zinc‐Ion Battery via Synergistically Electronic and Structural Regulation of a MnO2 Nanocrystal–Carbon Hybrid Framework. Issue 10 (17th January 2023) - Xu, Xilian; Chen, Ye; Li, Wanrui; Yin, Ruilian; Zheng, Dong; Niu, Xinxin; Dai, Xiaojing; Shi, Wenhui; Liu, Wenxian; Wu, Fangfang; Wu, Min; Lu, Shengli; et al.
Abstract: Aqueous rechargeable zinc‐ion batteries (ZIBs) have attracted burgeoning interests owing to the prospect in large‐scale and safe energy storage application. Although manganese oxides are one of the typical cathodes of ZIBs, their practical usage is still hindered by poor service life and rate performance. Here, a MnO2 –carbon hybrid framework is reported, which is obtained in a reaction between the dimethylimidazole ligand from a rational designed MOF array and potassium permanganate, achieving ultralong‐cycle‐life ZIBs. The unique structural feature of uniform MnO2 nanocrystals which are well‐distributed in the carbon matrix leads to a 90.4% capacity retention after 50 000 cycles. In situ characterization and theoretical calculations verify the co‐ions intercalation with boosted reaction kinetics. The hybridization between MnO2 and carbon endows the hybrid with enhanced electrons/ions transport kinetics and robust structural stability. This work provides a facile strategy to enhance the battery performance of manganese oxide‐based ZIBs. Abstract : A novel MnO2 nanocrystal–carbon hybrid is rationally constructed for the cathode of zinc‐ion battery, which possesses an ion‐permeable and robust network to achieve fast electrochemical kinetics, achieving ultralong cycle stability over 50 000 cycles and high specific capacity of 346.7 mAh g −1 at 0.5 A g −1 .